2003
DOI: 10.2307/3802677
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Segregation of Wolves from Humans in the Bialowieza Forest (Poland)

Abstract: Knowledge about the impact of human activity on the behavior of wolves (Canis lupus) is important to predict habitats suitable for wolf recolonization and for planning management zones. We tested the hypothesis that wolves live spatiotemporally segregated from humans. From 1994 to 1999, we radiotracked 11 wolves in 4 packs and monitored human activity in the Bial / owiez. a Forest, Poland. Wolves avoided permanent human-made structures (settlements, forest edge to arable land, roads, tourist trails) more in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
104
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 17 publications
(26 reference statements)
12
104
1
2
Order By: Relevance
“…This is consistent with increased ungulate abundance in areas of young vegetation (Peek et al 1976;Stelfox et al 2001*), which attract Wolves (Bergerud 1988). However, increased road access into these areas may also allow humans to alter activity patterns of Wolves (Theuerkauf et al 2003), or affect Wolf numbers by direct or indirect killing (Mech 1995, Mladenoff andSickley 1998). In this study, the least used habitat by Wolves was non-forest anthropogenic (pipelines, right-of-ways), possibly to avoid human contact.…”
Section: Discussionsupporting
confidence: 59%
“…This is consistent with increased ungulate abundance in areas of young vegetation (Peek et al 1976;Stelfox et al 2001*), which attract Wolves (Bergerud 1988). However, increased road access into these areas may also allow humans to alter activity patterns of Wolves (Theuerkauf et al 2003), or affect Wolf numbers by direct or indirect killing (Mech 1995, Mladenoff andSickley 1998). In this study, the least used habitat by Wolves was non-forest anthropogenic (pipelines, right-of-ways), possibly to avoid human contact.…”
Section: Discussionsupporting
confidence: 59%
“…Consistent with wolf movement in other areas, they selected low use trails (Thurber et al 1994) likely because they offered easy travel routes across the study area with low probabilities of encountering people (Musiani et al 1998, James and Stuart-Smith 2000, Callaghan 2002, Whittington et al 2005, Hebblewhite 2006). Conversely, the wolves avoided areas near the resort and weakly avoided trails with high levels of human use, presumably to minimize the probability of encountering people (Thurber et al 1994, Theuerkauf et al 2003a, Whittington et al 2005. When wolves shifted their movement following restoration, they increased their use of low elevations, shallow slopes, and high prey abundance, suggesting corridor creation increased the area of high quality habitat available to wolves within the study area.…”
Section: Resources Important To Wolves and Change In Resource Usementioning
confidence: 99%
“…Wolves are particularly important carnivores because they affect prey populations (Hebblewhite et al 2002, Hebblewhite et al 2005) and can cause ripple down effects in ecosystems (McLaren andPeterson 1994, Hebblewhite et al 2005). Wolves are a conservation priority because they incur higher risk of mortality due to their wide-ranging movements (Callaghan 2002), they are sensitive to habitat fragmentation (Weaver et al 1996, Mladenoff et al 1999, and they avoid areas with high levels of human activity (Callaghan 2002, Theuerkauf et al 2003a,b, Kaartinen et al 2005, Whittington et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect habitat loss caused by avoidance of trails and roads has been documented for wolves (Canis lupus; Theuerkauf et al 2003, Whittington et al 2004, consistent with this species treating human disturbance as predation risk, perhaps because of higher mortality near humans despite protection (Hebblewhite et al 2003). For elk (Cervus canadensis), however, responses were more variable; where some authors reported avoidance (Cassirer et al 1992, others reported selection for areas near human activity (Hebblewhite et al 2005), suggesting that both avoidance and trophic interaction may occur in different populations.…”
Section: Introductionmentioning
confidence: 99%
“…However, most previous research on the effects of human activities on wolf and elk selection has occurred at relatively coarse spatial-temporal scales. For example, previous research that has used human activity models at broad spatial scales includes Theuerkauf et al (2001), Anderson et al (2005), and Shively et al (2005). Research using human activity models at broad temporal scales, i.e., summer vs. winter, includes Jedrzejewski et al (2001) and Sawyer et al (2007).…”
Section: Introductionmentioning
confidence: 99%